PENERAPAN MANAJEMEN PROGRAM IMUNISASI LANJUTAN (BOOSTER) PADA ANAK BAWAH DUA TAHUN (BADUTA) DI PUSKESMAS PELABUHAN SAMBAS KOTA SIBOLGA TAHUN 2019 - Tiurlan, Mestika (Jurnal Inovasi Kesehatan Masyarakat, 2021)
Immunization is a form of health service that aims to reduce morbidity and mortality in children under five caused by PD3I. Complete Basic Immunization (IDL) and Advanced Immunization (Booster) in children under two years (Baduta) at the Pelabuhan Sambas Publics Health Center have reached the target but PD3I cases remain to be found, in 2019 there was a Diphtheria Incident (KLB) and an increase in Measles cases ( 17 cases). This study is a qualitative research with descriptive analytic methods. Which aims to analyze the application of management of the advanced imunization program (booster) to the Pelabuhan Sambas Publics Health Center in Sibolga City which includes P1(Palnning), P2(Implementation), P3(Monitoring and evaluation). The research sample was taken by purposive sampling technique. Data obtained through in-depth interviews and observation. The informants consisted of the main informants namely the Head of the Public Health Center, the immunization coordinator, the vaccine cold chain manager and the immunization implementing officer. Head of Health Service, Head of Disease Prevention and Control Division (P2P), Head of Immunization Surveillance Section, mothers who have Baduta, and cadre of posyandu toddlers as triangulation informants. The results showed that the vaccine Cold Chain Manager and immunization implementers had not received immunization training. Refrigerators and facilities at posyandu toddlers are in poor and adequate condition. Recording and reporting are not on time, and there are gaps between the baduta who receive advanced immunization services and those reported. This also proves that supervision, monitoring and evaluation activities have not been implemented well